2019
DOI: 10.1136/rmdopen-2019-001079
|View full text |Cite
|
Sign up to set email alerts
|

Treatment retention of infliximab and etanercept originators versus their corresponding biosimilars: Nordic collaborative observational study of 2334 biologics naïve patients with spondyloarthritis

Abstract: ObjectiveAlthough clinical trials support equivalence of originator products and biosimilars for etanercept and infliximab, real-world studies among biologics-naïve patients with spondyloarthritis (SpA) are lacking. The objectives were to compare treatment retention in biologics-naïve patients with SpA starting either the originator product or a biosimilar of infliximab and etanercept, and to explore the baseline characteristics of these patients.MethodsPatients with SpA (ankylosing spondylitis/non-radiographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…Lindström et al observed 1015 patients who primarily had spondyloarthritis. No increase in disease activity was observed in these patients 6 months after switching from Enbrel to Benepali ( 10 ). The same conclusion was reached by Holroyd et al, who followed‐up 92 adult patients with various rheumatic diseases for at least 6 months after switching from Enbrel to Benepali ( 22 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Lindström et al observed 1015 patients who primarily had spondyloarthritis. No increase in disease activity was observed in these patients 6 months after switching from Enbrel to Benepali ( 10 ). The same conclusion was reached by Holroyd et al, who followed‐up 92 adult patients with various rheumatic diseases for at least 6 months after switching from Enbrel to Benepali ( 22 ).…”
Section: Discussionmentioning
confidence: 81%
“…Both studies showed equivalent efficacy and safety of the biosimilars compared with the originator. In addition, extensive observational studies involving several thousand adult participants have been conducted for both switching from the originator to an etanercept biosimilar during the therapy course and starting therapy with an etanercept biosimilar ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current recommendations for AxSpa and PsA include this class of drugs on the same line as other mechanisms of action and based on this TNF inhibitors will be mentioned as comparators, as shown in Table 2 (43,44). Besides the anti-TNFa therapies approved in the last 20 years for the treatment of SpA patients (45)(46)(47), with proved efficacy also for the treatment of extraarticular manifestations such as uveitis (RAPID-axSpA ClinicalTrials.gov Identifier: NCT01087762) (48), biosimilars of TNFa inhibitors have become increasingly used, and observational studies of biologics-naïve patients with SpA have shown similar response and safety in patients treated with originators versus biosimilars, indicating comparable effects in clinical practice (49).…”
Section: Other Mechanisms Of Action In Axspa Therapiesmentioning
confidence: 99%
“…Besides the anti-TNFα therapies approved in the last 20 years for the treatment of SpA patients ( 45 47 ), with proved efficacy also for the treatment of extraarticular manifestations such as uveitis (RAPID-axSpA Identifier: NCT01087762) ( 48 ), biosimilars of TNFα inhibitors have become increasingly used, and observational studies of biologics-naïve patients with SpA have shown similar response and safety in patients treated with originators versus biosimilars, indicating comparable effects in clinical practice ( 49 ).…”
Section: Other Mechanisms Of Action In Axspa Therapiesmentioning
confidence: 99%
“…However, its scope covers only 3 countries of similar geographical and socio‐economic conditions (France, Belgium, and the Netherlands) 8 . Even if great efforts are being made in order to carry out joint studies of different registries that allow for greater generalizability of results, this research is still subject to problems due to the different methodologies used by said registries, leading to sample bias 12 or lack of comparability of the relevant indicators for axSpA patients’ health 13 …”
Section: Introductionmentioning
confidence: 99%